Gêneros textuais - Correia , Concebida Mendes da Silva; Lourdes , Dayane Freitas de; Cruz , Florisvaldo Gonçalves da; Silva, Maria Sinforosa Martin da; Carraro, Márcia Regina Simpioni (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf